Level of FABP3, FABP4, Nt-proBNP and Total Cardiovascular Risk in the Population of Central Kazakhstan - Marchenko, Alexandr Borisovich; Nildibayeva, Farida Ustarovna; Sorokina, Marina Anatolevna; Laryushina, Elena Mihaylovna; Turgunova, Lyudmila Gennadevna; Turmukhambetova, Anar Akyilbekovna (Open access Macedonian journal of medical sciences, 2017)
AIM: The study analyzed the level of cytokines playing the significant role in the diagnosis of circulatory system diseases and total cardiovascular risk.MATERIAL AND METHODS: The study involved 1,244 residents of Karaganda region. We had studied baseline participant characteristics, in addition to calculating the total cardiovascular risk and assessment of Fatty Acid Binding Proteins 3 (FABP3), Fatty Acid Binding Proteins 4 (FABP4) and N-Terminal Prohormone of Brain Natriuretic Peptide (NT-proBNP) level.RESULTS: The results showed the combination of high cardiovascular risk (CVR) with increased titers of cardiac markers, reflecting common pathogenic mechanisms in its development, among residents of Karaganda region.CONCLUSION: The combination of high CVR with the increased titers of cardiac markers showed common pathogenic mechanisms in its development, and support the diagnostic and prognostic value of these parameters among residents of Karaganda region, and also reflects the possibility to include these cardiac markers in the program of screening survey of population for early prevention of cardiovascular disease and its complications.